2014
DOI: 10.1071/cp12425
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial impacts of climate change on pastoral and broadacre agriculture in cool-temperate Tasmania

Abstract: Abstract. Although geographically small, Tasmania has a diverse range of regional climates that are affected by different synoptic influences. Consequently, changes in climate variables and climate-change impacts will likely vary in different regions of the state. This study aims to quantify the regional effects of projected climate change on the productivity of rainfed pastoral and wheat crop systems at five sites across Tasmania. Projected climate data for each site were obtained from the Climate Futures for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(39 reference statements)
1
4
0
1
Order By: Relevance
“…This is partly due to frost and other factors such as low solar radiation. Our results demonstrate that by 2050 pasture production in summer will likely be reduced as a result of further reductions in soil moisture and increases in vapour pressure deficit (Guobin and Kemp, 1992;Turner and Asseng, 2005), consistent with the previous findings of Phelan et al (2014) and Holz et al (2010) for Tasmanian pastures and Cullen et al (2009Cullen et al ( , 2012 for pasture in Victoria and New South Wales. Overall our results show that climate change between the baseline and 2050 will be beneficial for whole farm milk production since higher temperatures are conducive to greater pasture growth in winter and early spring, leading to greater annual biomass production.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is partly due to frost and other factors such as low solar radiation. Our results demonstrate that by 2050 pasture production in summer will likely be reduced as a result of further reductions in soil moisture and increases in vapour pressure deficit (Guobin and Kemp, 1992;Turner and Asseng, 2005), consistent with the previous findings of Phelan et al (2014) and Holz et al (2010) for Tasmanian pastures and Cullen et al (2009Cullen et al ( , 2012 for pasture in Victoria and New South Wales. Overall our results show that climate change between the baseline and 2050 will be beneficial for whole farm milk production since higher temperatures are conducive to greater pasture growth in winter and early spring, leading to greater annual biomass production.…”
Section: Discussionsupporting
confidence: 92%
“…The CFT modelling projections for Tasmania under the A2 emission scenario indicate temperature increases from 2.6°C to 3.3°C, and in some regions either positive or negative changes in annual rainfall of up to 100 mm per year . Previous studies of climate change impacts across the dairy regions of southeastern Australia have commonly focused on impacts on pasture and fodder crops (Bell et al, 2013;Cullen et al, 2009Cullen et al, , 2012Holz et al, 2010;Pembleton et al, 2013;Phelan et al, 2014). Cullen et al (2009Cullen et al ( , 2012 indicated that pasture production in cooltemperate climates would be relatively resilient to climate change, whilst Holz et al (2010) and Phelan et al (2014) suggest that the net effect of a warming climate would be beneficial for pasture growth.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although it has not previously been applied for climate change scenario analysis in the context of Nordic countries, APSIM has an open source code, is supported by an active user and developer community, and most importantly, already includes useful submodules to simulate the crops assessed in this study and the effects of changes in precipitation and temperature on the phenology and yield of the crops. Examples of APSIM being used for such tasks include Pembleton et al (2016), Phelan et al (2014), or Bahri et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…A wide number of crop models have been developed since the middle of the 20th century and the pioneering work of Cornelis Teunis de Wit [9,10]. Crop models can be used to perform various tasks such as predicting the effects of climate change on crops (e.g., [11][12][13]), optimization of farming practices for given soil-climate-crop combinations (e.g., [14,15]), understanding the environmental stresses experienced by crops (e.g., [16,17]) or to improve the knowledge of the physiological processes of a plant (e.g., [18]).…”
Section: Introductionmentioning
confidence: 99%